Assessing the Academic Performance of College Football Players through the Use of Multiple Measures: A Six-Year Follow-up Study - Robinson, Daniel C.; Goldman, Moses (My University, 1988)
The purpose of this study was to examine the influence of a variety of academic success variables as they relate to the academic performance of Division I football student-athletes. Through studying a group of incoming freshman football student-athletes at a large midwestem university, it was the goal of this study to analyze the influence of scores from the Nelson-Denny reading test (NDRT), the Minnesota Scholastic Aptitude test (MSAT), the Brown-Holtzman Survey of study habits and attitudes (SSHA), ACT, and high school rank (HSR) on the academic success of each participant, referred to as academic success variables. All Fall 1981 incoming freshmen who participated in revenue-producing sports (N = 49) were administered the above tests. ACT and HSR were obtained from the university's admissions office. The students' academic success was analyzed six years after their entrance into the university. Academic success was based upon the students' college GPA, how long they persisted within the university (LDOA), and whether or not they graduated. An analysis of the data showed that when compared on the basis of scores earned on various measures, those student-athletes who achieved higher scores were more successful in terms of college GPA, the amount of time they stayed in school, and whether or not they obtained a degree. This study supports the common belief that scores obtained on traditional college predictors may be good indicators of a student-athlete's chances of performing well at the university level. A positive relationship was found between college GPA and ACT scores as well as HSR.
Keywords: academic predictors